Legal Force of Under-Hand Deeds Legalized by a Notary - Setiadinanti, Syakina; Shallman, Shallman (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This study aims to analyze the comparative legal force between private deeds legalized by a notary and those not legalized, and to examine the responsibilities and legal protections for notaries in this process. Notaries, as public officials, have important authority to provide legal certainty by verifying signatures and confirming the legalization date on private deeds. The approach used in this research is a statute approach. This type of research is normative. The data used in this study are secondary data obtained through literature review and supported by information from a notary in Tegal. The research concludes: 1) A legalized deed has a stronger position because the notary guarantees that the signature is authentic and the date of its creation is certain. However, this legalization does not change the status of a private deed into an authentic deed, but can strengthen the evidentiary value of the deed if a dispute arises in the future. 2) The notary's responsibility in legalizing a private deed is limited to formal aspects, namely ensuring the accuracy of the signature, the identity of the parties, and the certainty of the date, not to the contents of the agreement. A notary can be held accountable if in carrying out his duties there is negligence or violation of applicable provisions. However, as long as the notary carries out his authority in accordance with laws and regulations and the code of ethics, the notary obtains legal protection, including through the role of the Notary Honorary Council which regulates the procedure for summoning a notary in legal proceedings.